Stemocurtisine, the first pyrido[1,2-a]azapine Stemona alkaloid - Mungkornasawakul P. (2014)
A new pentacyclic stemona alkaloid, stemocurtisine (2), with a novel pyrido [1,2-a]azapine A,B-ring system, has been isolated from a root extract of Stemona curtisii. The structure and relative stereochemistry was determined by spectral data interpretation and X-ray crystallography.